Acute necrotic cardiomyopathy in dogs anesthetized with ketamine and xylazine - case report - M.E. Hammerschmitt; P.R. Pereira; R.A. Caprioli; E.R. Monteiro; S.P. Pavarini; D. Driemeier (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2025)
ABSTRACT The combination of xylazine and ketamine has been used for decades to anesthetize dogs and cats undergoing surgical procedures. Three dogs died two to four days after being anesthetized with this combination without any know complications during the anesthetic procedure. White multifocal areas were present in the hearts of the three dogs, which histologically corresponded to marked necrosis of cardiomyocytes. Epidemiological and anatomopathological findings suggest that the dogs died because of cardiac impairment caused by the anesthetic combination.